2018
DOI: 10.3390/catal8040165
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Ketone Reduction by Immobilized Rhodotorula mucilaginosa

Abstract: In our previous study, Rhodotorula mucilaginosa (R. mucilaginosa) was selected via high throughput screening as a very active and selective whole-cell biocatalyst for the asymmetric reduction of ketones. In this study, the reduction of ketones to the desired chiral alcohols by immobilized cells of this strain was investigated. Characterization with Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) showed that whole R. mucilaginosa cells were successfully immobilized on suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The described storage conditions enabled the retention of 80% activity after about 10 months. High-throughput screening performed by Liu et al [36] revealed Rhodotorula mucilaginosa as a very active and selective whole-cell biocatalyst for the asymmetric reduction of various aromatic ketones to the desired chiral alcohols. For cell immobilization, agar, calcium alginate, PVA-alginate, and chitosan were employed as support matrices; pH tolerance and thermal stability were improved.…”
Section: This Special Issuementioning
confidence: 99%
“…The described storage conditions enabled the retention of 80% activity after about 10 months. High-throughput screening performed by Liu et al [36] revealed Rhodotorula mucilaginosa as a very active and selective whole-cell biocatalyst for the asymmetric reduction of various aromatic ketones to the desired chiral alcohols. For cell immobilization, agar, calcium alginate, PVA-alginate, and chitosan were employed as support matrices; pH tolerance and thermal stability were improved.…”
Section: This Special Issuementioning
confidence: 99%
“…Enantiopure secondary alcohols are valuable and versatile precursors for the production of chiral drugs . Benzofurans with numerous application areas are bicyclic ring structures .…”
Section: Introductionmentioning
confidence: 99%
“…Enantiopure alcohols are valuable and versatile building blocks for the manufacturing of chiral pharmaceuticals [1]. (R)-1- phenyl]ethanol is a crucial enantiomerically enriched intermediate for the production of AD101 (SCH-350581), a chemokine CCR5 antagonist widely used in AIDS patients to inhibit the replication of HIV-1 via blockade of its entry into cells [2].…”
Section: Introductionmentioning
confidence: 99%